Dual catalytic performance of arene-ruthenium amine complexes for norbornene ring-opening metathesis and methyl methacrylate atom-transfer radical polymerizations - Cruz, Thais R. [UNESP]; Silva, Eliada A.; Oliveira, Douglas P. [UNESP]; Martins, Daniele M.; Gois, Patrik D.S. [UNESP]; Machado, Antonio E.H.; Maia, Pedro Ivo S.; Goi, Beatriz E. [UNESP]; Lima-Neto, Benedito S.; Carvalho-Jr, Valdemiro P. [UNESP] (Wiley, 2020)
Arene ruthenium(II) complexes bearing the cyclic amines RuCl2(η6-p-cymene)(pyrrolidine)] (1), [RuCl2(η6-p-cymene)(piperidine)] (2), and [RuCl2(η6-p-cymene)(peridroazepine)] (3) were successfully synthesized. Complexes 1–3 were fully characterized by means of Fourier transform infrared, UV–visible, and NMR spectroscopy, elemental analysis, cyclic voltammetry, computational methods, and one of the complexes was further studied by single crystal X-ray crystallography. These compounds were evaluated as catalytic precursors for ring-opening metathesis polymerization (ROMP) of norbornene (NBE) and atom-transfer radical polymerization (ATRP) of methyl methacrylate (MMA). NBE polymerization via ROMP was evaluated using complexes 1–3 as precatalysts in the presence of ethyl diazoacetate (EDA) under different [NBE]/[EDA]/[Ru] ratios, temperatures (25 and 50°C), and reaction times (5–60 min). The highest yields of polyNBE were obtained with [NBE]/[EDA]/[Ru] = 5000/28/1 for 60 min at 50°C. MMA polymerization via ATRP was conducted using 1–3 as catalysts in the presence of ethyl-α-bromoisobutyrate (EBiB) as initiator. The catalytic tests were evaluated as a function of the reaction time using the initial molar ratio of [MMA]/[EBiB]/[Ru] = 1000/2/1 at 95°C. The increase in molecular weight as function of time indicates that complexes 1–3 were able to mediate the MMA polymerization with an acceptable rate and some level of control. Differences in the rate of polymerization were observed in the order 3 > 2 > 1 for the ROMP and ATRP.
Keywords: ATRP; olefin; p-cymene; ROMP; ruthenium